1996
DOI: 10.1038/nm1296-1382
|View full text |Cite
|
Sign up to set email alerts
|

Pyridostigmine brain penetration under stress enhances neuronal excitability and induces early immediate transcriptional response

Abstract: Pyridostigmine, a carbamate acetylcholinesterase (AChE) inhibitor, is routinely employed in the treatment of the autoimmune disease myasthenia gravis. Pyridostigmine is also recommended by most Western armies for use as pretreatment under threat of chemical warfare, because of its protective effect against organophosphate poisoning. Because of this drug's quaternary ammonium group, which prevents its penetration through the blood-brain barrier, the symptoms associated with its routine use primarily reflect per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
204
1
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 341 publications
(210 citation statements)
references
References 25 publications
4
204
1
1
Order By: Relevance
“…In addition, these veterans also showed lower salivary cortisol levels than their non-PTSD counterparts suggesting dysregulated immune system functioning (Kellner et al, 1999). However, we were unable to confirm any health complications from the synergistic effects of small doses of neurotoxicants combined with a stress induced reduction in immune functioning (Friedman et al, 1996) in our original evaluation of 200 GW veterans. In sum, there are several competing hypotheses for the varied symptoms reported by PGW veterans.…”
Section: Effects Of Stress On Physical Healthmentioning
confidence: 68%
See 1 more Smart Citation
“…In addition, these veterans also showed lower salivary cortisol levels than their non-PTSD counterparts suggesting dysregulated immune system functioning (Kellner et al, 1999). However, we were unable to confirm any health complications from the synergistic effects of small doses of neurotoxicants combined with a stress induced reduction in immune functioning (Friedman et al, 1996) in our original evaluation of 200 GW veterans. In sum, there are several competing hypotheses for the varied symptoms reported by PGW veterans.…”
Section: Effects Of Stress On Physical Healthmentioning
confidence: 68%
“…Other researchers suggest that prolonged stress can lead to long-term hormonal changes (Yehuda, 1997), reduced immune system functioning, (Black, 1994) and alterations of brain neurotransmitters that mediate cognitive and psychological responses (Wolfe & Charney, 1991). Reports of animal models suggest that acute stress may also alter the permeability of the blood brain barrier to particular neurotoxicants (including pyridostigmine bromide; an acetylcholinesterase inhibitor given prophylactically to PGW veterans as a protective measure in the event of chemical weapon attack (Friedman et al 1996). However, other reports of different rodent species could not replicate these findings (Lallement, 1998 ).…”
Section: Effects Of Stress On Physical Healthmentioning
confidence: 99%
“…The brain data show some significant differences consistent among all pesticide exposures. PYB does not easily pass the rodent blood-brain barrier, even under stressed conditions (31,32), although one study suggests otherwise (33). The compounds, even in total, remain at tracer concentrations (~100 nM maximum whole-body average for PYB) that can cause only minor competitive inhibition of proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Kaufer and colleagues 25 showed that acute stress of even moderate intensity (eg, a single session of 4 min forced swimming in mice)-as well as inhibitors of acetylcholinesterase (AChE)-produce a transient increase in the amount of released ACh in corticohippocampal areas, independent of the pituitary-adrenocortical axis. 26 Consequences include an early phase of enhanced neuronal excitability, 27 and most interest-ingly, long-lasting (up to 3 h in vitro) modulation of the genetic regulation of ACh availability 25 in the CNS. More specifically (see Figure 1), following acute stress and ACh release, the central muscarinic receptors mediate the induction of the gene encoding the early immediate transcription factor c-Fos.…”
Section: Why the Cholinergic System Can Be Important In Panic Attacksmentioning
confidence: 99%
“…More specifically (see Figure 1), following acute stress and ACh release, the central muscarinic receptors mediate the induction of the gene encoding the early immediate transcription factor c-Fos. 27 This produces, by a Ca 2+ -dependent mechanism, enhanced c-Fos binding to a site close to the promoter regions of genes with key roles for acetylcholine function, namely the gene encoding acetylcholinesterase (AchE), the gene for the acetylcholine-synthetizing enzyme choline acetyltransferase (ChAT), and the vescicular acetylcholine transporter (VAChT). RNA analyses clearly show 25 that more AChE is then produced, while synthesis of both ChAT and VAChT decreases.…”
Section: Why the Cholinergic System Can Be Important In Panic Attacksmentioning
confidence: 99%